2002
DOI: 10.1143/jjap.41.4450
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance 348 nm AlGaN/GaN-Based Ultraviolet-Light-Emitting Diode with a SiN Buffer Layer

Abstract: A 348 nm ultraviolet-light-emitting diode (UV-LED) based on an AlGaN/GaN single quantum well (SQW) with a high optical power is reported. In this structure, a thin SiN buffer is introduced before the growth of a conventional low-temperature GaN buffer layer. Such a buffer layer can dramatically reduce the density of threading dislocation as we have previously reported. Since the optical performance of UV-LED is generally known to be sensitive to the density of threading dislocations, unlike the InGaN/GaN-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…It was found that the lifetime of 365 nm UV LEDs depends strongly on dislocation density. The activation energy of UV LEDs with dislocation density of 1x10 8 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the lifetime of 365 nm UV LEDs depends strongly on dislocation density. The activation energy of UV LEDs with dislocation density of 1x10 8 …”
Section: Resultsmentioning
confidence: 99%
“…The ELO process, however, is a highly complex process. Therefore, it is desired to grow GaN films with dislocation density of less than 1x10 8 …”
Section: /Cmmentioning
confidence: 99%
“…It has been found recently that threading dislocations reduce the light output of UV LEDs much more than they do for blue GaN LED's [1][2][3][4]. Also for laser diodes a low density of dislocations is essential for extensions of their lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Especially for the ultraviolet light-emitting devices, it is very difficult to grow high performance ultraviolet MQWs on sapphire substrate. The point is totally different from InGaN-based blue/green LEDs because the performance of InGaN/GaN-based blue/green LED is not so sensitive to dislocations [3,4]. The insensitiveness of blue/green LED to the existed dislocation has been generally accepted to be due to the localization of excitons at certain potential minima, such as InGaN quantum dots [5] or quantum disks [6], formed by fluctuation of indium composition in InGaN QWs [7].…”
mentioning
confidence: 99%